“SLOW LEARNERS- A UNIVERSAL PROBLEM AND PROVIDING EDUCATIONAL OPPORTUNITIES TO THEM TO BE A SUCCESSFUL LEARNER” - Korikana, Appaji (PEOPLE: International Journal of Social Sciences, 2020)
Education plays an important role in a country’s development. Parents strongly feel that learning should be cultivated among their children. A teacher can make this become true with his teaching efficiency. But sometimes they may fail to do such due to different reasons. There are different types of learners such as fast learners, average learners, and slow learners. This learning difficulty may arise from poor memory, unawareness about the importance of education and lack of fundamental knowledge and psychological factors. If the teacher can bring out the children’s inner talents through the use of different conditions, slow learners will be happier at learning. This article tries to solve this universal problem by applying an inspiring quote from the universal scientist Albert Einstein saying "I never teach my pupils. I only attempt to provide the conditions in which they can learn". Data was collected through the Case study method. Counseling was used as a tool for their enhancement. The major finding was that slow learners were more successful by providing suitable conditions and educational opportunities to them.